2018
DOI: 10.1007/s10973-018-7564-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and kinetics of thermal degradation of insulating materials developed from cellulose fiber and fire retardants

Abstract: The mechanism and kinetics of thermal degradation of materials developed from cellulose fiber and synergetic fire retardant or expandable graphite have been investigated using thermogravimetric analysis. The model-free methods such as Kissinger-Akahira-Sunose (KAS), Friedman, and Flynn-Wall-Ozawa (FWO) were applied to measure apparent activation energy (E a). The increased E a indicated a greater thermal stability because of the formation of a thermally stable char, and the decreased E a after the increasing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Similar tests were performed by Zheng et al [27], with a temperature increase of 5 °C/min. The course of EG thermal decomposition is represented by the thermogravimetric (TG) (Figure 4) and derivative thermogravimetric (DTG) (Figure 5) curves.…”
Section: Eg As Fire Retardant Additive In Different Materialssupporting
confidence: 53%
See 2 more Smart Citations
“…Similar tests were performed by Zheng et al [27], with a temperature increase of 5 °C/min. The course of EG thermal decomposition is represented by the thermogravimetric (TG) (Figure 4) and derivative thermogravimetric (DTG) (Figure 5) curves.…”
Section: Eg As Fire Retardant Additive In Different Materialssupporting
confidence: 53%
“…The presence of expandable graphite (EG) greatly improves the char formation rate and quality in FR systems. Based on this literature review, it can be assumed that the incrustation of cellulose with expandable graphite may be of particular importance in the context of the thermal resistance of its amorphous areas [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of analysis is helpful for understanding the thermal stability of insulation materials and establishing their aging and fire-retardant characteristics. Zheng et al, [51] produced a thermal insulation material using cellulose pulp, whose fire retardancy was developed using an intumescent fire retardant, and its activation energy 𝐸𝐸 𝑎𝑎 increased due to the formation of thermally stable char. Later, Lie et al, [52] conducted a kinetic analysis of thermal insulator waste in the form of extruded polystyrene to learn more about its fire retardancy and recycling potential.…”
Section: Kinetic Analysismentioning
confidence: 99%
“…One challenge is that poor reaction-to-fire properties of foamformed materials need to be improved to meet the fire safety regulations. Zheng et al [160][161][162] showed that foamed cellulose insulation panels with commercial fire retardants (20% expandable graphite or 25% synergetic) passed fire class E according to the standard EN 13501-1. They also tested if coating of foam-formed materials would improve fire retardancy.…”
Section: Thermal Insulationmentioning
confidence: 99%